2016
DOI: 10.1002/ecs2.1217
|View full text |Cite
|
Sign up to set email alerts
|

The role of local and regional processes on population synchrony along the gradients of habitat specialization

Abstract: Citation: Pandit, S. N., K. Cottenie, E. C. Enders, and J. Kolasa. 2016. The role of local and regional processes on population synchrony along the gradients of habitat specialization. Ecosphere 7(5):e01217. 10. 1002/ecs2.1217 Abstract. Metacommunity perspective highlights the role of space as a factor contributing to local community structure and dynamics. Often tests of metacommunity models rely on snapshot patterns of species distribution and abundance. Such patterns may introduce biases because they ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…We also found evidence for the assertion that the dynamics of abiotic variables are more synchronous than those of biological variables. Finally, we found that environmental distance was the main predictor of synchrony, reinforcing the power of the Moran effect (Koenig, ; see also Pandit et al., for a similar result using environmental synchrony). The importance of environmental similarity in synchronising population dynamics has often been suggested (Haynes et al., ) and observed in several aquatic ecosystems (Cottenie, Michels, Nuytten, & De Meester, ; Kent, Yannarell, Rusak, Triplett, & McMahon, ; Seebens et al., ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also found evidence for the assertion that the dynamics of abiotic variables are more synchronous than those of biological variables. Finally, we found that environmental distance was the main predictor of synchrony, reinforcing the power of the Moran effect (Koenig, ; see also Pandit et al., for a similar result using environmental synchrony). The importance of environmental similarity in synchronising population dynamics has often been suggested (Haynes et al., ) and observed in several aquatic ecosystems (Cottenie, Michels, Nuytten, & De Meester, ; Kent, Yannarell, Rusak, Triplett, & McMahon, ; Seebens et al., ).…”
Section: Discussionsupporting
confidence: 83%
“…Spatial synchrony (or temporal coherence) occurs when data on different local populations (e.g., abundance), communities (e.g., species richness) or ecosystems (e.g., primary productivity) are significantly correlated across time. Several studies have demonstrated that synchrony is a common pattern that occurs in different regions (temperate and tropical), ecosystem types (e.g., aquatic and terrestrial) and groups of organisms (Allstadt, Liebhold, Johnson, Davis, & Haynes, ; Bjørnstad, Ims, & Lambin, ; Defriez & Reuman, ; Defriez, Sheppard, Reid, & Reuman, ; Ims & Andreassen, ; Koenig, ; Lansac‐Tôha et al., ; Moran, ; Pandit, Cottenie, Enders, & Kolasa, ; Ranta, Kaitala, Lindstrom, & Linden, ; Vogt, Rusak, Patoine, & Leavitt, ). For example, since the seminal works by Magnuson, Benson, and Kratz (), Kratz et al.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented taxonomic variability in the strength of freshwater plankton spatial synchrony (Rusak et al 1999;Lansac-Tôha et al 2008;Rusak et al 2008;Vogt et al 2011;Seebens et al 2013;Lodi et al 2014;Pandit et al 2016), but many previous studies were unable to explore multiple mechanisms, timescale structure, or geography of synchrony in explaining this taxonomic variability. We demonstrated that synchrony has an important timescale structure and a geography that will both complicate and enrich efforts to compare synchrony among species and to understand the causes and consequences of synchrony.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies of synchrony in freshwater plankton also have generally examined synchrony between different water bodies (Rusak et al ; Rusak et al ; Vogt et al ; Pandit et al ), rather than within a single water body. Using separate water bodies limits comparative investigations of drivers of synchrony (i.e., dispersal, predation, and Moran effects), as dispersal among lakes is unlikely to be sufficient to synchronize their plankton dynamics.…”
mentioning
confidence: 99%
“…Our study complements the bulk of existing studies of synchrony in freshwater plankton in part because most previous studies have examined synchrony of populations in different water bodies, and we examine synchrony within one large reservoir. Most studies of spatial synchrony of freshwater plankton among different water bodies have supported distance-decay relationships, Moran-effect causes of synchrony, and/or species-specific variability in the strength of synchrony (Magnuson et al 1990, Rusak et al 1999, Vogt et al 2011, Pandit et al 2016). Dispersal as a mechanism of synchrony has typically been less of a focus in between-lake synchrony studies because it is unlikely that synchrony would arise from this mechanism between lakes: dispersal between lakes is probably very limited in numbers of organisms transferred.…”
Section: Introductionmentioning
confidence: 99%